Recent advances in the study of reproductive function in pediatric patients with brain tumors - Zhang, Rui; Liu, Linlin; Dai, Xinyu; Ju, Yan; Ren, Yanming (Frontiers in Pediatrics, 2025)
In recent years, pediatric brain tumors have emerged as one of the most common malignant tumors among children. The site of tumor growth and the selected treatment modalities can potentially have a profound and significant impact on the reproductive function of pediatric patients, which is intimately associated with the physical and psychological health of children during their developmental process. Current research studies have demonstrated that pediatric patients diagnosed with germ cell tumors, craniopharyngiomas, and medulloblastomas commonly present with reproductive dysfunction. Regrettably, in clinical practice, neurosurgeons frequently fail to allocate sufficient attention to this particular aspect. It is of critical and urgent necessity to explore and elucidate the alterations in reproductive function among pediatric patients with brain tumors, and subsequently institute essential protective measures. This article is dedicated to comprehensively reviewing the latest research advancements regarding the relationship between pediatric brain tumors and reproductive function, thereby providing a valuable reference for safeguarding the reproductive function of pediatric patients afflicted with brain tumors.